Ï‰6/Ï‰3 Polyunsaturated fatty acid supplementations in renal cell model lead to a particular regulation through lipidome for preserved Ï‰6/Ï‰3 ratios - Fares, M.; Armand, M.; Francois, C.; Maixent, J. M. (Cellular and Molecular Biology, 2012)
Polyunsaturated fatty acids (PUFA) supplementations modify cell lipid composition leading to a change in cell function. However, the effect of PUFA supplementations in renal model cell on the kidney epithelial cells membrane fatty acid profile is not known. Therefore, the purpose of this study was to determine the effects of PUFAs with different Ï‰6/Ï‰3 ratios supplementations in the kidney epithelial cells and the type of supplementation that can be used as cellular protection during kidney transplantation. For that, we used as model the LLCPK-1 cell and determined their membrane fatty acid (FA) composition after supplementation with three different commercial food supplements. These supplements consist of S1: docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) with Ï‰6/Ï‰3 ratio = 0.1, S2: DHA, EPA, linoleic acid (LA) and Î³-linoleic acid (GLA) with Ï‰6/Ï‰3 ratio = 2.5, or S3: Î±-linolenic acid (ALA) and LA with Ï‰6/Ï‰3 ratio near 1. Cells were incubated for 24 hr with 30 µM of Ï‰3 fatty acids from each supplement. Fatty acid composition of control and experimental groups was analysed by gas chromatography after extraction of lipids and fatty acids methylation. The efficiency of cell PUFA supplementation was achieved by showing 2 to 4 fold increases in cell PUFA incorporation. Whatever the supplementation used, the cell saturated fatty acids (SFA) were decreased by 50% following the three supplementations used (p<0.001) as compared to control group. These decreases in SFA were compensated in part by increasing monounsaturated fatty acid levels. All these changes were observed with constant of cell Ï‰6/Ï‰3 ratio whatever the supplementations used. These data suggest that the supplements, with long chain polyunsaturated fatty acids or their precursors, lead to important regulation in the lipidome (desaturases and elongases) associated to preserved Ï‰6/Ï‰3 ratios. The fatty acids remodeling may represent an interesting new mechanism by which renal FA homoestasis could occurred.